Association of orexin receptor polymorphisms with antipsychotic-induced weight gain. (2nd April 2016) - Tiwari, Arun K.; Brandl, Eva J.; Zai, Clement C.; Goncalves, Vanessa F.; Chowdhury, Nabilah I.; Freeman, Natalie; Lieberman, Jeffrey A.; Meltzer, Herbert Y.; Kennedy, James L.; Müller, Daniel J.
Abstract: Objectives : Antipsychotic-induced weight gain (AIWG) is a common side effect of treatment with antipsychotics such as clozapine and olanzapine. The orexin gene and its receptors are expressed in the hypothalamus and have been associated with maintenance of energy homeostasis. In this study, we have analysed tagging single nucleotide polymorphisms (SNPs) in orexin receptors 1 and 2 (HCRTR1 and HCRTR2) for association with AIWG. Methods : Schizophrenia or schizoaffective disorder subjects ( n  = 218), treated mostly with clozapine and olanzapine for up to 14 weeks, were included. Replication was conducted in a subset of CATIE samples ( n  = 122) treated with either olanzapine or risperidone for up to 190 days. Association between SNPs and AIWG was assessed using analysis of covariance (ANCOVA) with baseline weight and duration of treatment as covariates. Results : Several SNPs in HCRTR2 were nominally associated with AIWG in patients of European ancestry treated with either clozapine or olanzapine ( P <0.05). In the replication analysis two SNPs rs3134701 ( P  = 0.043) and rs12662510 ( P  = 0.012) were nominally associated with AIWG. None of the SNPs in HCRTR1 were associated with AIWG. Conclusion : This study provides preliminary evidence supporting the role of HCRTR2 in AIWG. However, these results need to be confirmed in large study samples.